GARCH modelling of cryptocurrencies - Jeffrey Chu; Stephen Chan; Saralees Nadarajah; Joerg Osterrieder (Journal of Risk and Financial Management, 2017)
With the exception of Bitcoin, there appears to be little or no literature on GARCH modelling of cryptocurrencies. This paper provides the first GARCH modelling of the seven most popular cryptocurrencies. Twelve GARCH models are fitted to each cryptocurrency, and their fits are assessed in terms of five criteria. Conclusions are drawn on the best fitting models, forecasts and acceptability of value at risk estimates.
Keywords: 330; exchange rate; maximum likelihood; value at risk